2020
DOI: 10.3390/molecules25040778
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Desorption Properties of Total Flavonoids from Oil Palm (Elaeis guineensis Jacq.) Mature Leaf on Macroporous Adsorption Resins

Abstract: Three different macroporous resins (XAD7HP, DAX-8, and XAD4) were evaluated for their adsorption and desorption properties in preparing flavonoid-enriched oil palm (Elaeis guineensis Jacq.) leaf extract. The influences of initial concentration, solution pH, contact time, and desorption solvent (ethanol) concentration were determined by static sorption/desorption methods. The optimal condition for adsorption of flavonoids was achieved when the solution of the extract was adjusted to pH 7, reaching equilibrium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 37 publications
7
59
0
Order By: Relevance
“…The optimal pH value was around 5, which resulted in an increased enrichment of the N. lotus stamen extract in total flavonoids. This result is consistent with other studies [55][56][57][58][59][60]. At a higher pH value, the flavonoid phenolic hydroxyl groups dissociated with H+ and the corresponding flavonoid anion result in lower adsorption capacity and thus a drastic reduction in the purification yield [57].…”
Section: Optimization Of Macroporous Resin Purification Of Total Flavsupporting
confidence: 92%
See 4 more Smart Citations
“…The optimal pH value was around 5, which resulted in an increased enrichment of the N. lotus stamen extract in total flavonoids. This result is consistent with other studies [55][56][57][58][59][60]. At a higher pH value, the flavonoid phenolic hydroxyl groups dissociated with H+ and the corresponding flavonoid anion result in lower adsorption capacity and thus a drastic reduction in the purification yield [57].…”
Section: Optimization Of Macroporous Resin Purification Of Total Flavsupporting
confidence: 92%
“…The results showed that concentration and pH of the aqEtOH solution and the temperature influenced the desorption capacity of the MPR. In the literature, most flavonoids are desorbed with an aqEtOH concentration for the desorption solution ranging from 75-100% (v/v) in agreement with the present study [54][55][56][57][58][59][60]. The pH value can change the ionization of flavonoids, which also affects their adsorption to the MPR [57].…”
Section: Optimization Of Macroporous Resin Purification Of Total Flavsupporting
confidence: 88%
See 3 more Smart Citations